A microcontroller-based system for patient and elderly community assistance. (18th February 2022) - Chotani, Asmita; Jain, Rakshit; Naresh, K.; Anitha, K.; Goyal, Ranjan
Generally, the elderly community is bedridden due to age parameters and health issues. Thus, there is a need for a system which can be an aid for this group. In this paper, a microcontroller-based system model is proposed. This system model assists the patients and elderly community by providing them the facility to satisfy their needs by informing the attenders/wards through a handheld device. Depending upon the frequency generated for a key press, a particular need is triggered among the set of predefined needs to the facilitator in terms of the audio from the device, which is mounted within his proximity.